Information Literacy from High School to University : Report of the Ontario School Library Impact Project (OSLIP) - Cavanagh, Mary; Oberg, Dianne; Buchansky, Heather; D'Avernas, Marc; Johnson-McGregor, Kate; Roberts, Sarah (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2021)
The Ontario School Library Impact Project (OSLIP) investigated the impact of school libraries on the development of key information literacy skills in students entering post-secondary education, using online surveys and qualitative interviews. The project found that first-year university students are challenged by the demands of post-secondary course research assignments. These findings support previous research indicating first-year university students are challenged by new demands for research skills. Unfortunately, opportunities to develop those skills are inconsistent among school boards in Ontario. This is a multifaceted problem confronting both school librarians and academic librarians as well as their teaching partners.